2013
DOI: 10.1007/s10919-013-0158-9
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Synchronization in Naturally Occurring Settings: A Recurrence-Based Analysis of Gaze Directions and Speech Rhythms of Staff and Clients with Intellectual Disability

Abstract: Past research has shown that rapport and cooperation between individuals is related to the level of nonverbal synchrony they achieve in their interactions. This study investigates the extent to which staff and clients with mild to borderline intellectual disability achieve interactional synchrony in daily social interactions. Whilst there has been work examining how staff can adapt their verbal communication to help achieve better mutual understanding, there has been an absence of work concerning the responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Dominance in this context is the level of influence a person has on the course of the interaction, for example, by taking the initiative. However, Reuzel, Embregts, Bosman, Cox, et al (2013) and Reuzel et al (2014) found that the clients with an ID appeared to be more sensitive to attunement, namely, synchronisation of nonverbal behaviour.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Dominance in this context is the level of influence a person has on the course of the interaction, for example, by taking the initiative. However, Reuzel, Embregts, Bosman, Cox, et al (2013) and Reuzel et al (2014) found that the clients with an ID appeared to be more sensitive to attunement, namely, synchronisation of nonverbal behaviour.…”
Section: Introductionmentioning
confidence: 98%
“…In recent studies, Reuzel, Embregts, Bosman, Cox, et al (2013), Reuzel et al (2014), investigated interactional patterns between staff and people with a mild to borderline ID during routine meetings. Reuzel and her colleagues investigated the attunement of staff and people with an ID both on a content and a process level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, several methodological advances made these techniques more appropriate for the analysis of categorical data, for instance as collected in the behavioral sciences. As a result CRQA has found its way into the study of interpersonal behavior, and has now been applied successfully to explore, for instance, syntactic coordination between children and parents [5,6], eye movement synchronization between speakers and listeners [7,8], mother-infant gaze during a still-face procedure [9], infant-parent visual coordination in joint attention [10], nonverbal attunement in social interaction [11][12][13], and transitions in parent-child conflict conversation due to intervention [14]. In all these cases CRQA has provided valuable and unique knowledge about interpersonal coordination and its relation to other psychological constructs or its development.…”
Section: Introductionmentioning
confidence: 99%
“…More often than not effective and efficient interpersonal coordination requires individuals to behave quite differently from each other and sometimes even perform opposite actions in a coupled way (e.g. [11][12][13][14][15][16][17][18][19][20][21]). In addition, frequently behavioral scientists wish to keep track of, distinguish between, and relate several behavioral atoms, and wish to distil their temporal structure.…”
Section: Introductionmentioning
confidence: 99%